Found schools to consolidate the Republic and shape citizens. An approach to the case of Colombia, 1819-1825 - Pita Pico, Roger (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
The nascent republican government undertook efforts to give greater importance to primary schools. These institutions were conceived not only as a level of basic shaping for the cultural and intellectual development of citizens, but also as an enabling space to enthrone society under liberal and republican principles. The ambitious coverage plans in primary education ran into a hostile environment marked by the economic crisis, the fiscal deficit, and the political-military tension all this amid a fragile and fluctuating administrative structure. This situation led to propose new and varied forms of financing, which involved a more active support and commitment from the community and government agencies at local scale.